2010
DOI: 10.1021/jp110202e
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Discrete/Continuum Linear Response Shells Theory of Solvation: Convergence Test for NH4+ and OH Ions in Water Solution Using DFT and DFTB Methods

Abstract: A new dynamical discrete/continuum solvation model was tested for NH(4)(+) and OH(-) ions in water solvent. The method is similar to continuum solvation models in a sense that the linear response approximation is used. However, different from pure continuum models, explicit solvent molecules are included in the inner shell, which allows adequate treatment of specific solute-solvent interactions present in the first solvation shell, the main drawback of continuum models. Molecular dynamics calculations coupled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 75 publications
(129 reference statements)
2
27
0
Order By: Relevance
“…Thus, it is highly desirable to develop more general theories of hybrid discrete‐continuum solvation. The shells theory of solvation is another hybrid approach . Essentially, the solvent is divided in two shells: S 1 and S 2 .…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is highly desirable to develop more general theories of hybrid discrete‐continuum solvation. The shells theory of solvation is another hybrid approach . Essentially, the solvent is divided in two shells: S 1 and S 2 .…”
Section: Theorymentioning
confidence: 99%
“…This method is relatively expensive because it involves generation of several configurations followed by single point quantum mechanical calculations. For example, in the study of the solvation of small ions, 500 snapshots were selected for the ensemble average. Despite this high computational cost, it was successfully applied in the study of the hydroxylamine isomerization equilibrium in aqueous solution .…”
Section: Theorymentioning
confidence: 99%
“…Given that a QM treatment of solvent might be desirable, the careful researcher may next wonder how much solvent should be treated quantum mechanically. A number of studies have explored this question for different molecular properties, [61][62][63][64][65][66] and the study of convergence of excitation energies with increasing size of molecular environment has become an area of active research. [10][11][12][67][68][69] Although in some systems a large amount of QM solvent may not be critical for accurately computing the property of interest, we have found that for excited states, values within approximately 0.05 eV of the converged value can be obtained with a full solvation shell treated with QM, as shown in Figure 3.…”
Section: Combining Qm Explicit Solvent With Classical Solvent Modelsmentioning
confidence: 99%
“…The nitrogen atom acts as a base, receiving a proton of the attacking nucleophilic atom, whereas the oxygen atom acts as an acid, forming a hydrogen bond with the carbonyl oxygen and transferring the proton. 8 The most recent study by Lima et al 9 using Shells Theory of Solvation (STS) 10,11 has predicted that the neutral form is 3.5 kcal mol −1 more stable. In the next step, the -NH 3 + group moves to the phenoxide oxygen and induces the breakdown of the tetrahedral intermediate.…”
Section: Introductionmentioning
confidence: 99%